Geology and U-Pb geochronology of the Annidale Group, southern New Brunswick: Lower Ordovician volcanic and sedimentary rocks formed near the southeastern margin of lapetus Ocean - McLeod, M.; Ruitenberg, A.; Krogh, T. (Atlantic Geology, 1992)
Geological mapping and U-Pb (zircon) dating have led to the discovery of distinctive Lower Ordovician volcano-sedimentary rocks in the Annidale area of southern New Brunswick. These rocks are included in a newly defined group, herein termed the Annidale Group, which is divided into three fault bounded(?) units of partially overlapping age. These units are named the East Scotch Settlement Formation, the Lawson Brook Formation and the Canaan Forks sequence, from south to north. The East Scotch Settlement Formation contains a steeply dipping succession of mixed mafic and felsic volcanic rocks and a variety of clastic and volcanogenic sedimentary rocks. The Lawson Brook Formation constitutes a shallowly to moderately north-dipping succession dominated by felsic volcanic rocks. The Canaan Forks sequence, most of which constitutes a shallowly to moderately north-dipping succession, is dominated by clastic sedimentary rocks. Structurally, much of the Annidale Group is characterized by intense shearing produced by numerous vertical northeast- and northwest-trending faults and by southward- and northward-directed thrust faults. In the vicinity of these structural features, the East Scotch Settlement Formation is further characterized by pervasive carbonatization that is commonly accompanied by base-metal- and gold-bearing silicification and high chromium-mica alteration zones. Zircons from a felsic dome in the East Scotch Settlement Formation and from felsic schists in the Lawson Brook Formation yield U-Pb dates of 493 ± 2 Ma and 497 ±10 Ma, respectively. Based on these dates and constituent lithologies, the Annidale Group is tentatively correlated with parts of the Cookson Group to the southwest.